Aplikasi Sistem Administrasi Inventarisasi dan Peminjaman Barang Berbasis Android: Application for Inventory Administration and Item Borrowing System Based on Android - Rangga Satria Wirabangsa; Dwi Ratnasari; Giri Wahyu Wiriasto (Depertment of Electrical Engineering University of Mataram, 2023)
Management information systems (MIS) have an important role in managing data. This article discusses the development of MIS applications that are used to facilitate the management of goods rental transaction data in government institutions. Usually the rental process is written in the tenant's register book, besides that the condition of the goods being rented cannot be monitored in real time. This MIS was developed in the form of a web-based server and Android mobile application. Webserver base application, used as the main database system and as an admin page when doing data updating work. Meanwhile, the mobile-based application provides a rental report data resume page that is recorded regularly and will be needed by executives. The advantage of this mobile basis is that the lessee can easily apply for a practical rental of goods. If approved, the tenant comes directly to the office to pick up the goods and complete the rental documents. Webserver-based applications are developed using PHP and mobile applications are developed using Kotlin. While the API interface uses the REST method. Tests carried out are in the form of alpha-testing to test the running application system and beta-testing for user satisfaction. The percentage of alpha and beta testing results was 100% and 88.60%.